Celebrating user involvement in research. (1st April 2011) - Rainey, P; Morris, C; Kendall, M; Murray, S A; Cameron, D
Abstract : Abstract: Background: This year the scientific committee has examined abstract submissions for evidence of User Involvement that is, ▶ Present from the early stages of the research cycle (eg, generating ideas, prioritising, study design). ▶ Collaborative – working as co-researchers – not simply commenting on completed work. ▶ Innovative – (eg, presenting to funding/ethics boards undertaking interviews, leading dissemination in some areas). ▶ And has created a tangible output which has contributed to the conduct of the study (eg, protocol writing, higher recruitment, richer data). Aims: To highlight and acknowledge those researchers who have demonstrated a high level of commitment to User Involvement in their work. To emphasise the importance of collaborating with service users in research and to offer some insight into the future of User Involvement in SUPAC research. Methods: Professor David Cameron, Clinical Director at the Edinburgh Cancer Research Centre and former Director of NCRN, will reflect on the significance of User Involvement during his time at NCRN and offer some personal insight into how best SUPAC research might flourish. Following this talk, three shortlisted candidates for this year's User Involvement Award will take part in a short discussion about their work, following which a presentation will be made to the winner.